Analisis Nilai-Nilai Humanis dalam Kurikulum Pesantren dan Relevansinya bagi Pendidikan Modern di MAN 1 Banyuwangi - Istibana, Istibana; Aimah , Siti (Jurnal Pendidikan Indonesia (JOUPI), 2024)
This article analyzes humanist values ​​in the pesantren curriculum and their relevance to modern education, with a case study at MAN 1 Banyuwangi. This study aims to explore how humanist values, such as tolerance, independence, social responsibility, and character building, are integrated into the pesantren curriculum and adapted into the context of formal education in madrasahs. A qualitative approach was used in this study, with data collection techniques in the form of in-depth interviews, observations, and document analysis. The results of the study indicate that the pesantren curriculum at MAN 1 Banyuwangi not only instills Islamic values ​​but also emphasizes humanist aspects that are relevant to facing the challenges of globalization and modernization. The implementation of these values ​​creates an inclusive learning environment, oriented towards the holistic development of student potential, and supports the creation of a generation with noble character and competence in the modern era. This study concludes that humanist values ​​in the pesantren curriculum have significant relevance in enriching the modern education approach, especially in building student character based on spiritual and moral values.